mTOR downregulation promotes anti-inflammatory responses via the CCL3-CCR5 axis in hypoxic retinopathy - Tae Kwon Moon; Im Kyeung Kang; Kyoung Jin Lee; Ji Hyun Kim; Hee Jong Kim; A. Reum Han; Ha-Na Woo; Joo Yong Lee; Jun-Sub Choi; Keerang Park; Heuiran Lee (Molecular Therapy: Methods & Clinical Development)
Hypoxic retinopathies, including diabetic retinopathy, are major contributors to vision impairment, mainly due to accelerated angiogenesis and inflammation. Previously, we demonstrated that AAV2-shmTOR, effective across distinct species, holds therapeutic promise by modulating the activated mTOR pathway, yet its mechanisms for reducing inflammation remain largely unexplored. To investigate AAV2-shmTOR’s impact on atypical inflammation in these conditions, we employed an in vivo model of oxygen-induced retinopathy and an in vitro model using rMC1 Müller cells. AAV2-shmTOR notably decreased mTOR expression in rMC1 cells under hypoxic conditions, as verified by co-staining for mTOR and glial fibrillary acidic protein (GFAP). It effectively interrupted the activation of mTOR signaling triggered by hypoxia. It diminished the secretion of CCL3 from rMC1 cells, consequently reducing microglial migration in response to conditioned media from AAV2-shmTOR-treated rMC1 cells. Notably, the virus lowered CCL3 expression in Müller cells and reduced the presence of CCR5-positive microglia in vivo, indicating its effectiveness in targeted inflammation management via the CCL3-CCR5 pathway. These findings thus highlight the potential of AAV2-shmTOR to exert anti-inflammatory effects by influencing the mTOR and subsequent CCL3-CCR5 pathways in hypoxic retinopathies, presenting a novel therapeutic approach for retinal diseases marked by hypoxia-driven inflammation.